Genetic Variants and Functional Analyses of the ATG16L1 Gene Promoter in Acute Myocardial Infarction - Han, Falan; Pang, Shuchao; Sun, Zhaoqing; Cui, Yinghua; Yan, Bo (Frontiers in Genetics, 2021)
Background: Acute myocardial infarction (AMI), a common complex disease caused by an interaction between genetic and environmental factors, is a serious type of coronary artery disease and is also a leading cause of death worldwide. Autophagy-related 16-like 1 (ATG16L1) is a key regulatory factor of autophagy and plays an important role in induced autophagy. In the cardiovascular system, autophagy is essential to preserve the homeostasis and function of the heart and blood vessels. No studies have hitherto examined the association between AMI and ATG16L1 gene promoter. Methods: We conducted a case-control study, using polymerase chain reaction and sequencing techniques, dual luciferase reporter assay, and electrophoretic mobility shift assay to analyze genetic and functional variation in the ATG16L1 gene promoter between AMI and controls. A variety of statistical analyses were used to analyze the allele and genotype frequencies and the relationship between single-nucleotide polymorphisms (SNPs) and AMI. Results: In all, 10 SNPs and 2 DNA-sequence variants (DSVs) were identified in 688 subjects, and 3 ATG16L1 gene promoter mutations (g.233250693 T>C [rs185213911], g.233250946 G>A [rs568956599], g.233251133 C>G [rs1301744254]) that were identified in AMI patients significantly altered the transcriptional activity of ATG16L1 gene promoter in HEH2, HEK-293, and H9c2 cells (P < 0.05). Further electrophoretic mobility shift assays indicated that the SNPs affected the binding of transcription factors (P < 0.01). Conclusions: ATG16L1 gene promoter mutations in AMI patients may affect the binding of transcription factors and change the transcriptional activity of the ATG16L1 gene, changing the level of autophagy and contributing to the occurrence and development of AMI as rare and low-frequency risk factors.